The impact of Neo-Liberal frameworks on student mobility and internationalisation in African higher education - Woldegiorgis, E. T. (South African Journal of Higher Education, 2024)
Internationalization and academic mobility have traditionally been pivotal components within higher education, each serving distinct roles. Internationalization has been instrumental in promoting academic exchange, enabling knowledge dissemination, fostering research collaborations, and driving shared innovation. However, the emergence of neoliberal ideologies has embedded global capitalism’s market dynamics into higher education systems globally, aligning the sector increasingly with market-oriented values. This paper investigates the effects of neoliberalism on the internationalization of higher education in Africa, with particular emphasis on evolving trends in international student mobility. It contends that neoliberal influences on international mobility extend beyond mere market considerations, touching on issues of hegemony within global knowledge frameworks that often marginalize African nations and institutions. The study is based on published sources and accessible statistical data from governmental and non-governmental entities. By exploring the intersections of neoliberalism and internationalization in higher education, this paper highlights the complex and nuanced nature of these dynamics and their concrete implications for the movement of students across borders. Furthermore, the article considers how neoliberal entanglements may shape the future trajectory of internationalization within African higher education contexts.